Comparison of Two Types of Composite-Opaquer Combinations Masking Ability for Tooth Discoloration without Clinically Visible Opacity - Hossein Chalakinia; Farideh Darabi; Yasaman Sadeghi; Reza Tayefe Davalloo; Seyedeh Maryam Tavangar; Aidin Sooratgar (Journal of Dentistry)
Background: A few studies have examined the masking ability of the combined application of opaquer and resin composites on tooth discoloration.Purpose: This study investigated the combined application of opaquer-composite to mask discolored backgrounds by utilizing two opaquers and resin composites.Materials and Method: In this in vitro research, we used two composite resins, Vitalescence (Ultradent) and Gradia Direct (GC), and two opaquers: Pink opaque (Cosmedent) and Creative Color A2 (Cosmedent). Seventy-two specimens were made as disks in 8 groups (n=9), with 1.0mm and 0.5mm thicknesses. One surface of each disk was coated by one of the opaquers and cured. The 4mm-thick composite disks from both composite brands were also made as a reference, representing the inherent color of the material. Then, the composite disks from the opaquer-coated surface were placed on a C4 porcelain disk as a background to simulate a discolored tooth. Color measurement for all specimens was performed using a spectrophotometer device. The color difference of each test group and 4 mm thick disks of the same composite were measured using the formula CIELAB (ΔE * ab). Statistical analysis was performed by using ANOVA and Tukey's Post hoc tests.Results: Statistically significant differences were observed between the eight groups (p= 0.001). The thickness, composites, and opaquer variants significantly affected the ΔE*. The samples with 1mm thickness, the Vitalescence composite, and the Creative Color opaquer A2, had significantly lower ΔE* than the 0.5mm samples, the Gradia composite, and the Pink opaquer, respectively. The number of samples with desirable ΔE was significantly higher in the Vitalescence composite group than in the Gradia composite, and the Creative Color A2 opaquer had significantly more desirable ΔE than the Pink opaquer.Conclusion: Most results that achieved acceptable masking ability were obtained with combinations of Creative Color opaquer A2+ Vitalescence / Gradia composite in 0.5 or 1mm thicknesses.